PENGARUH GROWTH, SIZE, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B51109030, LIDIA PRAMITA (Jurnal KIAFE, 2013)
The purpose of this study was to determine the effect of growth, size, and profitability of the company's value either partially or simultaneously, as well as determine how much influence the growth, size, and profitability of the enterprise value of the foods and beverages company that are listed in the Indonesia Stock Exchange. The samples used in this study are food and beverage company listed on the Indonesia Stock Exchange in 2009-2011. Samples are 12 food and beverage companies, where the method used is purposive sampling is a sampling of research that takes an object by specifying certain criteria. While the method of analysis used is the technique of multiple linear regression analysis to determine the effect of independent variables on the dependent variable is done with the classical assumption that consist of normality test, multicollinearity, heterokedastisitas test and autocorrelation test. Hypothesis testing is performed using the F test and t test. Results of this study showed that partially (1) growth does not have a significant effect on the value of the company (2) size has no significant effect on firm value, (3) and profitability have a significant influence on firm value. All independent variables are growth, size, and profitability simultaneously significant effect on the dependent variable is the value of the company. On the other hand, 92.1% of the variation is explained by the variable value of the firm growth, size, and profitability. While 7.9% is influenced by other factors outside the regression model. Suggested to the next researcher to not examine food and beverage companies, it is suggested that further research be done to expand the sample of companies that include all kinds of companies listed on the Indonesia Stock Exchange. This study only uses variable growth, size, and profitability to determine the effect on firm value. for researchers to conduct further studies using other financial variables that have a greater impact on firm value. Keywords : Value of the Firm, Price Book Value, Growth, Size, Profitability, and Return On Equity